Using a combination of midazolam and butorphanol is a safe and effective reversible field sedation protocol for Weddell seal (Leptonychotes weddellii) pups. (17th October 2022) - Whoriskey, Sophie; Pearson, Linnea E.; Harris, Heather S.; Whitmer, Emily R.; Liwanag, Heather E. M.; Brodie, Erin; Johnson, Shawn
Abstract: Background: Weddell seals ( Leptonychotes weddellii ) are a well‐studied species of phocid with an apparent sensitivity to immobilising agents. Mortality as high as 31% has been reported during field immobilisation. This study investigated the use of a benzodiazepine in combination with an opioid agonist/antagonist for sedation in Weddell seal pups as part of a physiological study. Methods: During the 2017 and 2019 Antarctic pupping seasons, 18 Weddell seal pups were sedated by intramuscular administration of a combination of midazolam and butorphanol or intravenous midazolam alone. Individuals were sedated at 1, 3, 5 and 7 weeks of age. Naltrexone and flumazenil were used to reverse sedation. The combination was 100% effective in providing appropriate sedation for the intended procedures. Results: Analyses were performed to investigate relationships between dose administered, age, individual reactions, adverse effects and changes in dive physiology. Transient apnoea (10–60 seconds) was the most frequently observed adverse effect. No sedation‐associated morbidity or mortality occurred. Limitations: The sample size is small and there is no pharmacokinetic information for either sedative or reversal in phocid species. Conclusions: The combination of midazolam (0.2–0.3 mg/kg) and butorphanol (0.1–0.2 mg/kg) provided safe and effective sedation, with reversible effects, in Weddell seal pups.